Riboflavin Has Neuroprotective Potential: Focus on Parkinson’s Disease and Migraine - Marashly, Eyad T.; Bohlega, Saeed A. (Frontiers in Neurology, 2017)
• Abstract With the huge negative impact of neurological disorders on patient’s life and society resources, the discovery of neuroprotective agents is critical and cost-effective. Neuroprotective agents can prevent and/or modify the course of neurological disorders. Despite being underestimated, riboflavin offers neuroprotective mechanisms. Significant pathogenesis-related mechanisms are shared by, but not restricted to, Parkinson’s disease and migraine headache. Those pathogenesis-related mechanisms can be tackled through riboflavin proposed neuroprotective mechanisms. In fact, it has been found that riboflavin ameliorates oxidative stress, mitochondrial dysfunction, neuroinflammation, and glutamate excitotoxicity; all of which take part in the pathogenesis of Parkinson’s disease, migraine headache, and other neurological disorders. In addition, riboflavin-dependent enzymes have essential roles in pyridoxine activation, tryptophan-kynurenine pathway, and homocysteine metabolism. Indeed, pyridoxal phosphate, the active form of pyridoxine, has been found to have independent neuroprotective potential. Also, the produced kynurenines influence glutamate receptors and its consequent excitotoxicity. In addition, methylenetetrahydrofolate reductase requires riboflavin to ensure normal folate cycle influencing the methylation cycle and consequently homocysteine levels which have its own negative neurovascular consequences if accumulated. In conclusion, riboflavin is a potential neuroprotective agent affecting a wide range of neurological disorders exemplified by Parkinson’s disease, a disorder of neurodegeneration, and migraine headache, a disorder of pain. In this article, we will emphasize the role of riboflavin in neuroprotection elaborating on its proposed neuroprotective mechanisms in opposite to the pathogenesis-related mechanisms involved in two common neurological disorders, Parkinson’s disease and migraine headache, as well as, we encourage the clinical evaluation of riboflavin in Parkinson’s disease and migraine headache patients in the future.